Alcohol-Associated liver disease outcomes: critical mechanisms of liver injury progression - Osna, Natalia; Tikhanovich, Irina; Ortega-Ribera, Martí; Mueller, Sebastian; Zheng, Chaowen; Müller, Johannes; Li, Siyuan; Sakane, Sadatsugu; Weber, Raquel Carvalho Gontijo; Kim, Hyun Young; Lee, Wonseok; Ganguly, Souradipta; et al. (Biomolecules, 2024)
Alcohol-associated liver disease (ALD) is a substantial cause of morbidity and mortality worldwide and represents a spectrum of liver injury beginning with hepatic steatosis (fatty liver) progressing to inflammation and culminating in cirrhosis. Multiple factors contribute to ALD progression and disease severity. Here, we overview several crucial mechanisms related to ALD end-stage outcome development, such as epigenetic changes, cell death, hemolysis, hepatic stellate cells activation, and hepatic fatty acid binding protein 4. Additionally, in this review, we also present two clinically relevant models using human precision-cut liver slices and hepatic organoids to examine ALD pathogenesis and progression.
Gesehen am 28.01.2025